Assessing the Likelihood of High Pathogenicity Avian Influenza Incursion Into the Gamebird Sector in Great Britain via Designated Hatcheries - Fujiwara, Mayumi; Auty, Harriet; Brown, Ian; Boden, Lisa (Frontiers in Veterinary Science, 2022)
The outbreaks of High Pathogenicity Avian Influenza (HPAI) in the United Kingdom in 2017 and 2021 had a substantial impact on the gamebird industry and highlighted to policymakers the importance of existing knowledge gaps for effective disease control. Despite the size of the industry, the impact of HPAI on the gamebird industry is not well understood. To improve future disease preparedness, a veterinary risk assessment to explore the risk of HPAI incursion into the gamebird sector in Great Britain via a designated hatchery was commissioned by Scottish Government Animal Health and Welfare Division. Hatchery designation is a legal requirement for hatcheries located within disease control zones or that have business links to premises located in disease control zones to continue operating during an HPAI outbreak. Several risk pathways were identified, which involved various management procedures associated with egg production through to the delivery of day-old chicks. The overall likelihood of the HPAI virus introduction into a designated hatchery through hatching egg movement is considered to be low (high uncertainty). The overall likelihood of onward transmission of the HPAI virus into gamebird rearing sites from a designated hatchery through day-old chick movement is also considered to be low (medium uncertainty). These risk levels are based on the assumption that relevant control measures are observed, as enhanced biosecurity is one of the requirements for hatchery designation. However, high uncertainties and variabilities were identified in the level of compliance with these biosecurity measures. Factors increasing the likelihood level include management practices typical to this sector, such as having multiple egg production sites, raising birds at outdoor sites, catching birds from the wild for egg production, having various scale of satellite farms in various locations, importing eggs and day-old chicks from overseas, as well as the proximity of the game farm to the infected premise or to higher risk areas. This study offers evidence for policymakers to help develop criteria for hatchery designation and proposes important mitigation strategies for future disease outbreaks specific for the gamebird sector.